Repeated intravenous cardiosphere-derived cell therapy in late-stage Duchenne muscular dystrophy (HOPE-2): a multicentre, randomised, double-blind, placebo-controlled, phase 2 trial. Issue 10329 (12th March 2022) - McDonald, Craig M; Marbán, Eduardo; Hendrix, Suzanne; Hogan, Nathaniel; Ruckdeschel Smith, Rachel; Eagle, Michelle; Finkel, Richard S; Tian, Cuixia; Janas, Joanne; Harmelink, Matthew M; Varadhachary, Arun S; Taylor, Michael D; et al.
Summary: Background: Cardiosphere-derived cells (CDCs) ameliorate skeletal and cardiac muscle deterioration in experimental models of Duchenne muscular dystrophy. The HOPE-2 trial examined the safety and efficacy of sequential intravenous infusions of human allogeneic CDCs in late-stage Duchenne muscular dystrophy. Methods: In this multicentre, randomised, double-blind, placebo-controlled, phase 2 trial, patients with Duchenne muscular dystrophy, aged 10 years or older with moderate upper limb impairment, were enrolled at seven centres in the USA. Patients were randomly assigned (1:1) using stratified permuted blocks to receive CAP-1002 (1·5 × 10 8 CDCs) or placebo intravenously every 3 months for a total of four infusions. Clinicians, caregivers, patients, and clinical operations personnel were fully masked to treatment groups. The primary outcome was the change in mid-level elbow Performance of Upper Limb version 1.2 (PUL 1.2) score at 12 months, assessed in the intention-to-treat population. Safety was assessed in all individuals who received an investigational product. This trial is registered with ClinicalTrials.gov, NCT03406780. Findings: Between March 1, 2018, and March 31, 2020, 26 male patients with Duchenne muscular dystrophy were enrolled, of whom eight were randomly assigned to the CAP-1002 group and 12 to the placebo group (six were not randomised due to screening failure). In patients who had a post-treatment PUL 1.2 assessment (eight in the CAP-1002 group and 11 in the placebo group), the mean 12-month change from baseline in mid-level elbow PUL1.2 favoured CAP-1002 over placebo (percentile difference 36·2, 95% CI 12·7–59·7; difference of 2·6 points; p=0·014). Infusion-related hypersensitivity reactions without long-term sequelae were observed in three patients, with one patient discontinuing therapy due to a severe allergic reaction. No other major adverse reactions were noted, and no deaths occurred. Interpretation: CAP-1002 cell therapy appears to be safe and effective in reducing deterioration of upper limb function in patients with late-stage Duchenne muscular dystrophy. Various measures of cardiac function and structure were also improved in the CAP-1002 group compared with the placebo group. Longer-term extension studies are needed to confirm the therapeutic durability and safety of CAP-1002 beyond 12 months for the treatment of skeletal myopathy and cardiomyopathy in Duchenne muscular dystrophy. Funding: Capricor Therapeutics.